STRATEGI HOUSEKEEPING DALAM MENANGANI BED BUGS DI HOTEL BEVERLY BATAM - M. Gemi Rabil; Zahara Fatimah; Arina Luthfini Lubis; Supardi (Universitas Pendidikan Ganesha, 2025)
Bed bug infestation is a serious operational threat in the hotel industry because it directly affects guest comfort, service quality, and the hotel’s reputation on digital platforms. Inadequate or delayed handling may lead to recurring complaints and reduced guest trust. This study aims to analyze the housekeeping strategies used to prevent and manage bed bug infestations at the Beverly Batam Hotel as part of maintaining hygiene standards and service quality. A descriptive qualitative method was applied through observations, interviews, and documentation involving the housekeeping supervisor and staff. The findings reveal three key insights: (1) the hotel implements an integrated control strategy through routine inspections, isolation of suspected rooms, high-temperature linen processing, selective chemical treatment, and coordination with external pest control professionals; (2) early detection relies heavily on staff accuracy and experience, making continuous training a critical factor; and (3) high-occupancy periods reduce the consistency of SOP implementation due to limited time and manpower. Although the strategies applied have successfully prevented recurring cases, improvements are still needed in monitoring and guest education. These findings emphasize that bed bug management is not merely a technical issue but a managerial concern that requires a structured risk-mitigation approach. Practical implications include the need to establish a dedicated bed bug response team, digitize inspection checklists, and conduct regular training to ensure stable SOP implementation and effective control.